A three-parameter model for fatigue crack growth data analysis - A. De Iorio; M. Grasso; F. Penta; G.P. Pucillo (Fracture and Structural Integrity)
A three-parameters model for the interpolation of fatigue crack propagation data is proposed. It has been validated by a Literature data set obtained by testing 180 M(T) specimens under three different loading levels. In details, it is highlighted that the results of the analysis carried out by means of the proposed model are more smooth and clear than those obtainable using other methods or models. Also, the parameters of the model have been computed and some peculiarities have been picked out.